Analysis of the Temperature Variation of Bizarre Thermal Barrier Coatings and their impacts on Engine - Thirunavukkarasu Raja; Muji Setiyo; Veeramanikandan Murugan; Sathish Dhandapani (Universitas Muhammadiyah Magelang, 2023)
This article presents Ansys simulations and experimental testing to determine how TBC affects engine performance and emissions. In this work, two distinct thermal barrier coatings have been identified, and the same coating materials were subsequently sprayed onto the pistons of an internal combustion engine. Transient thermal analysis reveals that TBC-1 and TBC-2 coatings reduce surface temperature distributions by 35% and 18%, respectively, and that these engines improve Brake Thermal Efficiency (BTE) by 8.71% and 7.62%, respectively, compared to non-coated engines operating under full load. TBC-1 and TBC-2 coated engines are found to have Brake-Specific Fuel Consumption (BSFC) reductions of 27.13% and 18.81%, respectively. Complete combustion reduces emissions of CO and HC, as the heat balance sheet indicates because the conversion of energy and mechanical work are enhanced by 3.56 percentage points and 2.0 percentage points, respectively.